2016
DOI: 10.5812/ircmj.42638
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evaluation of the Effects of Nitrate in Drinking Water on Laminin Alpha-5 Expression in Rat Renal Glomeruli

Abstract: Background: Nitrate is a polyatomic ion with the molecular formula NO3 -. Nitrate poisoning occurs through metabolism in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Also, there was no significant difference in lamininα 5 expression among the group receiving water containing 45mg/L of nitrate compared to distilled water and control groups. However, they observed a significant increase in anti-lamininα 5 reaction in a group treated with water containing 100mg/L of nitrate compared to another group [25]. These results were not in line with our findings regarding the effects of hyperthyroidism on lamininα 5 gene expression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, there was no significant difference in lamininα 5 expression among the group receiving water containing 45mg/L of nitrate compared to distilled water and control groups. However, they observed a significant increase in anti-lamininα 5 reaction in a group treated with water containing 100mg/L of nitrate compared to another group [25]. These results were not in line with our findings regarding the effects of hyperthyroidism on lamininα 5 gene expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Mohammadi et al in a study using a mouse model showed that nicotine-induced immunohistochemical reaction of collagen IV in the alveolar BM of the control group changed from light brown to dark brown [23], and in a similar investigation on pulmonary alveoli, laminin expression significantly decreased in experimental groups compared to control groups [24]. Effects of nitrate in drinking water on laminin-α5 expression in rat renal glomeruli showed that by increasing the concentration of nitrate in drinking water of Wistar rats, the severity of the reaction of anti-laminin-α5 decreased in renal glomeruli [25]. Also, there was no significant difference in lamininα 5 expression among the group receiving water containing 45mg/L of nitrate compared to distilled water and control groups.…”
Section: Discussionmentioning
confidence: 90%
“…in a study using a mouse model showed that nicotine-induced immunohistochemical reaction of collagen IV in the alveolar BM of the control group changed from light brown to dark brown [ 23 ], and in a similar investigation on pulmonary alveoli, laminin expression significantly decreased in experimental groups compared to control groups [ 24 ]. Effects of nitrate in drinking water on laminin-α5 expression in rat renal glomeruli showed that by increasing the concentration of nitrate in drinking water of Wistar rats, the severity of the reaction of anti-laminin-α5 decreased in renal glomeruli [ 25 ]. Also, there was no significant difference in lamininα 5 expression among the group receiving water containing 45mg/L of nitrate compared to distilled water and control groups.…”
Section: Discussionmentioning
confidence: 99%